Risk Factors for Ectropion After Lower Eyelid and Cheek Reconstruction Following Mohs Micrographic Surgery - Jess D. Rames, MD, MEng; Melissa M. Rames, MD; Caroline Y. Yu, MD; Nicole Sanchez Figueroa, MD; Christeebela O. Akpala, RN; Sara Hussein, MD; Addison M. Demer, MD; Basel A. Sharaf, MD, DDS; Lilly H. Wagner, MD (Plastic and Reconstructive Surgery, Global Open)
Background:. Development of ectropion is a frequently reported complication after reconstruction of infraorbital Mohs defects. This study aimed to characterize preoperative and surgical factors contributing to ectropion development in patients undergoing reconstruction after Mohs micrographic surgery. Methods:. We conducted a retrospective single-center case-control study on patients undergoing reconstruction of Mohs micrographic surgery defects involving the nonmarginal lower eyelid and upper cheek from 2011 to 2023. Pre- and postoperative photographs were reviewed to confirm defect location and postreconstructive eyelid malposition. Ectropion risk factors were determined with uni- and multivariate odds ratio analyses. Results:. A total of 202 patients were included, 45 cases in the ectropion group and 157 in the control group. Negative orbital vector (P = 0.02), recurrent disease (P = 0.01), and greater defects size (P = 0.007) were associated with postreconstructive ectropion. Ectropion was more likely after multidisciplinary reconstruction (13.3% versus 1.4%, P < 0.001) and reconstruction with cervicofacial flaps (28.9% versus 4.2%, P < 0.0005); and less likely after primary closure (8.9% versus 28.5%, P < 0.001). Multivariate assessment (odds ratio [95% confidence interval], P value) revealed that combined cheek and eyelid defect involvement (4.32 [1.36–13.6], P = 0.01), larger size (1.07 [1.03–1.13], P < 0.001), and negative orbital vector (12.11 [2.65–65.42], P = 0.002) were independent risk factors for ectropion development. Conclusions:. Combined cheek/lower eyelid defects and negative orbital vector increase the risk of postreconstructive ectropion. These findings can be used to optimize surgical technique and counsel patients on increased likelihood of this complication with possible need for revision surgery.